2022
DOI: 10.1002/adhm.202201164
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Injectable Alginate and Poly(3,4‐ethylenedioxythiophene)‐Based Soft Electrodes toward the Goal of Neuro‐Regenerative Applications

Abstract: Resident brain neural precursor cells (NPCs) are electrosensitive cells that respond to electric field application by proliferating, differentiating, and undergoing rapid and directed cathodal migration. Harnessing NPC potential is a promising strategy to facilitate neural repair following injury or disease. The use of electric fields to activate NPCs is limited by current electrode designs which are typically made of conductive metals that are stiff and can lead to neuroinflammation following implantation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In this context, recent studies indicate the use of naturallyderived conductive biopolymers, such as 𝛾-polyglutamic acid (𝛾-PGA) in combination with PEDOT:PSS improves the biocompatibility, adhesiveness, conductivity (∼12.5 S m −1 ), self-healing (healing time 2 s), stretchability (up to ≈300%) and flexibility (>300 kPa stress, ≈650% strain) towards wearable bioelectronics fabrication. [158] Similarly, many recent studies demonstrated that the use of chitosan, [159] alginate, [160][161][162][163] gelatin, [164][165][166][167][168] and cellulose [169][170][171][172][173] with PEDOT:PSS improved the conductivity and biocompatibility of the composites.…”
Section: Pedot:pss and Its Nanocompositesmentioning
confidence: 99%
“…In this context, recent studies indicate the use of naturallyderived conductive biopolymers, such as 𝛾-polyglutamic acid (𝛾-PGA) in combination with PEDOT:PSS improves the biocompatibility, adhesiveness, conductivity (∼12.5 S m −1 ), self-healing (healing time 2 s), stretchability (up to ≈300%) and flexibility (>300 kPa stress, ≈650% strain) towards wearable bioelectronics fabrication. [158] Similarly, many recent studies demonstrated that the use of chitosan, [159] alginate, [160][161][162][163] gelatin, [164][165][166][167][168] and cellulose [169][170][171][172][173] with PEDOT:PSS improved the conductivity and biocompatibility of the composites.…”
Section: Pedot:pss and Its Nanocompositesmentioning
confidence: 99%
“…Current electrode designs, which are typically made of stiff conductive metals that can cause neuroinflammation after implantation in part due to the mechanical mismatch between implanted materials and physiological conditions, limit the use of electric fields to activate NPCs. In a study, alginate/PEDOT, a novel injectable biobased soft electrode with appropriate electrical stimulation characteristics, indicated a suitable blend matches with the brain tissue and negligible activation of inflammatory cells compared to traditionally used platinum-based electrodes [ 191 ].…”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…The kinetic stability of ncrys-PEDOT X was investigated by monitoring the absorbance of 1 wt% (10 mg mL −1 ) ncrys-PEDOT X aqueous dispersions over time (see the Experimental Section)-a common method to profile the sedimentation kinetics of nanomaterial dispersions. [36,37] Both ncrys-PEDOT 5 and ncrys-PEDOT 20 were first dispersed via stirring in either DI H 2 O or 2% aqueous sodium alginate, the latter of which is a common precursor for conductive biomaterials (Figure S2, Supporting Information); [38,39,40] such high filler concentrations are similar to those used with graphene oxide, and are orders of magnitude more concentrated than what can be achieved with untreated CNTs or G. For example, graphene nanoplatelets can only be dispersed in water without oxidation or complex surfactant optimization at concentrations less than 0.01 mg mL −1 . [41] In both DI and aqueous sodium alginate solutions the sedimen-tation of ncrys-PEDOT 5 and ncrys-PEDOT 20 were similar, however ncrys-PEDOT 5 had a relatively slower rate, potentially due to the elevated amount of PSS internal surfactant.…”
Section: Conductive Ncrys-pedot X Incorporated Hydrogelsmentioning
confidence: 99%